Protest Against Social Injustice In Charlotte Bronte's Jane Eyre - WINARSIH, SRI, Dr. M. Thoyibi, M.S, Dr. Phil. Dewi Candraningrum, M.Ed (2015)
Novel, as one kind of fiction, facilitate a man who called anauthor, as a member of society and a man who is given a talent to write, to expose what in her/his mind such social problem happens in society. Here, the novel functions as both giving pleasure and benefit. He/she has chance and competence to elevate even a horrible social problem to the worthy one through aesthetic works. That is the function of literature which Rene Wellek (1978) stated: "it is probable that all art is "sweet" and "useful" to its appropriate users: that what it articulates is superior to their own self-induced reverie or reflection(p. 21). This research aims to expose social injustice portrayed in Charlotte Bronte's Jane Eyre and to prove the author's protest against social injustice through the main character of this novel. This research is classified as a descriptive qualitative method. The primary data source of this research is the novel Jane Eyreby Charlotte Bronte (1848). This novel consists of 459 pages. The collecting data process is note-taking technique. So, this research is also categorized as library research. Based on the investigation on social injustice in Jane Eyre, the researcher draws conclusions such follows. There are nine social injustices portrayed in Jane Eyre i.e. neglected orphan, child abuse, rigid social class relation, erroneous impression of governess, harsh school regulation, health, disease and death, fallen women, disputed bequest, and faith versus human right . The result, the researcher found Charlotte Bronte's disapproval against the social injustice seen through the main character (Jane Eyre)'s views expressed in dialogues with supporting characters and narration. The disapproval promoted by the author in her struggle is to protest the social injustice and to change the dreadful conditions at that time to the better and valuable ones. It also influences the other character to care about such social injustice in the imaginary condition and revolutionize it. By applying the theory of sociology of literature, the researcher deems Jane Eyre is a historical document since it illustrates the evidences and happened in English society in the early nineteenth century.